지역 종합병원 간호사의 직무 스트레스가 건강증진행위에 미치는 영향 : 긍정심리자본과 간호근무환경의 매개효과 - 장유민; 박주영 (한국직업건강간호학회지, 2018)
Purpose: The purpose of this study is to provide preliminary data for alleviating nurses' job stress and support health promotion behaviors. Further, the study reviews the mediating effects of positive psychological capital and nursing work environment in relation to job stress and health promotion behaviors among nurses in a regional general hospital. Methods: A study survey was conducted from June 9 to 16, 2017. The subjects were current nurses working at a regional general hospital in D city. Analysis of a survey questionnaire from 147 participants was conducted. Results: Upon reviewing the mediating effects of positive psychological capital and nursing work environment in relation with health promotion behaviors and job stress, it was found that positive psychological capital (Z=-4.78, p<.001) and nursing work environment (Z=-4.17, p<.001) were significant mediators. Conclusion: As demonstrated through the results of this research, it is necessary to build programs to strengthen individual positive psychological capital and increase the practice of health promotion behaviors among nurses. It is also evident that a systematic approach is needed to improve the nursing work environment.